Sm0.5Sr0.5Co1−xNixO3−δ—A Novel Bifunctional Electrocatalyst for Oxygen Reduction/Evolution Reactions - Xingmei Liu; Yuwei Wang; Liquan Fan; Weichao Zhang; Weiyan Cao; Xianxin Han; Xijun Liu; Hongge Jia (Molecules, 2022)
The development of non-precious metal catalysts with excellent bifunctional activities is significant for air–metal batteries. ABO3-type perovskite oxides can improve their catalytic activity and electronic conductivity by doping transition metal elements at B sites. Here, we develop a novel Sm0.5Sr0.5Co1−xNixO3−δ (SSCN) nanofiber-structured electrocatalyst. In 0.1 M KOH electrolyte solution, Sm0.5Sr0.5Co0.8Ni0.2O3−δ (SSCN82) with the optimal Co: Ni molar ratio exhibits good electrocatalytic activity for OER/ORR, affording a low onset potential of 1.39 V, a slight Tafel slope of 123.8 mV dec−1, and a current density of 6.01 mA cm−2 at 1.8 V, and the ORR reaction process was four-electron reaction pathway. Combining the morphological characteristic of SSCN nanofibers with the synergistic effect of cobalt and nickel with a suitable molar ratio is beneficial to improving the catalytic activity of SSCN perovskite oxides. SSCN82 exhibits good bi-functional catalytic performance and electrochemical double-layer capacitance.